2013
DOI: 10.1590/s1413-81232013001200015
|View full text |Cite
|
Sign up to set email alerts
|

Utilização de medicamentos entre crianças de zero a seis anos: um estudo de base populacional no sul do Brasil

Abstract: Utilização de medicamentos entre crianças de zero a seis anos: um estudo de base populacional no sul do BrasilDrug use among children between zero and six years old: a population baseline study in the south of Brazil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1
9

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 16 publications
2
14
1
9
Order By: Relevance
“…6,8 Due to the heterogeneity of the methods used in other studies, it is difficult to compare the data, as the age group investigated and the recall period vary significantly, as well as the origin of the medication use. While some studies have investigated the use of medications by medical prescription, 3 others assessed their use in self-medication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,8 Due to the heterogeneity of the methods used in other studies, it is difficult to compare the data, as the age group investigated and the recall period vary significantly, as well as the origin of the medication use. While some studies have investigated the use of medications by medical prescription, 3 others assessed their use in self-medication.…”
Section: Discussionmentioning
confidence: 99%
“…25 Although some of the medications used to treat the respiratory tract, such as dexchlorpheniramine and the association of phenylephrine-brompheniramine are contraindicated for children younger than two years, it was observed that approximately 17.18% of children using these medications were in this age group. 8,26,27 In addition to the intrinsic adverse effects of each active substance, there are other factors that can make them potentially dangerous for this age group, including the incorrect dose interpretation or dose interval, use of inappropriate dispensing measures, or the simultaneous administration of several medications, in order to achieve greater symptom relief. 8,22 The authors also emphasize the significant use of nimesulide and diclofenac in children younger than 1 year, an age group for which the medication is contraindicated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Algumas revisões sistemáticas têm demonstrado que alguns desses medicamentos não apresentam benefício significativamente superior ao placebo no tratamento de síndromes das infecções de vias áreas superiores, como congestão nasal e rinorreia [40,41], tosse crônica inespecífica [42] e sinusite aguda [43]. Tais dados retratam a cultura regional de prevenir e tratar quadros de dor e febre, os quais muitas vezes podem ser contornados com medidas não medicamentosas [44].…”
Section: Artigo Originalunclassified
“…Quando avaliadas as classes ATC, verificou-se que a mais prescrita incluiu os medicamentos para o sistema nervoso, seguida de anti-infecciosos sistêmicos e dos medicamentos para trato digestivo e metabólico; e comparativamente a outros estudos, verificou-se uma semelhança nas classes mais utilizadas [10,[44][45][46]. Os anti-infecciosos sistêmicos aparecem na lista dos medicamentos mais utilizados por crianças em diversos estudos [47,48], e este é um resultado esperado ao considerar-se que as doenças infecciosas, especialmente as de vias respiratórias, estão entre as morbidades mais comuns em crianças, sendo responsáveis por grande parte das prescrições de antimicrobianos [49].…”
Section: Artigo Originalunclassified